(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
As the shift in the educational landscape continues to unfold, Higher Education Institutions develop and implement mechanisms that respond to the ever-changing and dynamic needs of their key stakeholders, the students. The study explored the effectiveness and relevance of clubs and organizations to the holistic development and well-being of the students in this flexible learning modality. Employing the mixed method, the data are gathered and analyzed from six hundred six (606) respondents of the seventeen (17) clubs and organizations from one of the private schools in Cagayan de Oro City. Descriptive Statistics were used to determine the effectiveness and relevance of the clubs and thematic analysis in delving into the qualitative responses. It was found that the school clubs and organizations are extremely relevant (M=4.30) to the students in all aspects. Data show that students from twelve (12) organizations out of sixteen (16) found them extremely effective (M=4.30) in promoting wellness and developing students holistically. Emerging themes identified as the contribution of clubs to their wellness are self-development, socialization and communication, recreation and stress alleviation, boosting mental health, and developing collaboration and leadership. This implied that clubs significantly help develop the multiple facets of students despite the virtual platform: